Pengaruh Bokashi Kotoran Sapi Terhadap Sifat Kimia Tanah Alfisol dan Hasil Jagung (Zea Mays L.) Lokal Muna - Sulistiawati, Novi; Darwis, Darwis; Resman, Resman; Hemon, M. Tufaila; Zulfikar, Zulfikar; Namriah, Namriah (CV. Eduartpia Publisher, 2023)
The purpose of this study was to determine the effect of feeding bokashi cow manure on the chemical properties of Alfisols soil and the yield of Muna's local corn (Zea Mays L.). This study was conducted at the Land Experiment Garden II Faculty of Agriculture of Halu Oleo University, and the sampling of Alfisol soil was conducted in Puwatu Village, from March to June 2022. This study used a Randomized Group Design (RGD) method with 4 bokashi cow manure treatments: B0 = without bokashi cow manure (control), B1 = 200 g polybag-1, B2 = 400 g polybag-1, B3 = 600 g polybag-1. The research results show that the treatment of bokashi manure improves the chemical properties of the soil. Treatment of B3 gives the highest values for organic-C (0.34%), total-N (0.11%), available-P (25.66 ppm), KTK (53.19 me/100g) except for available-K and affects plant height, stem diameter, fruit weight and seed count. Keywords : Alfisols, Bokashi, Muna Local Maize, Soil Fertili